Peningkatan Hasil Belajar Pendidikan Agama Islam Melalui Model Pembelajaran Problem Based Learning (PBL) pada Siswa Kelas X SMA Negeri 1 Pulau Banyak - Nur Ayu Bancin; Erlina Gea (Insight: Indonesian Journal of Social, Humanity, and Education, 2026)
The low learning outcomes in Islamic Religious Education among tenth-grade students at SMA Negeri 1 Pulau Banyak constitute the main research problem of this study. This condition is influenced by teacher-centered learning practices, limited student engagement, and the lack of contextual and problem-oriented learning models. This study aims to improve students’ learning outcomes and the quality of the learning process in Islamic Religious Education through the implementation of the Problem Based Learning (PBL) model. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were tenth-grade students of SMA Negeri 1 Pulau Banyak. Data were collected through learning achievement tests, classroom observations, and documentation. The findings reveal that the implementation of the Problem Based Learning model significantly improved students’ learning outcomes, as indicated by an increase in mastery learning from 40% in the pre-cycle to 60% in cycle I, and further to 87% in cycle II. In addition, problem-based learning enhanced students’ active participation, engagement, and deeper contextual understanding of Islamic Religious Education materials. The novelty of this study lies in the application of the Problem Based Learning model in Islamic Religious Education at the senior high school level, emphasizing not only cognitive achievement but also the development of critical thinking and religious problem-solving skills relevant to students’ daily lives. This study recommends the sustainable use of the PBL model as an effective and innovative instructional approach in Islamic Religious Education. [Rendahnya hasil belajar Pendidikan Agama Islam (PAI) pada peserta didik kelas X SMA Negeri 1 Pulau Banyak menjadi permasalahan utama dalam penelitian ini. Kondisi tersebut dipengaruhi oleh proses pembelajaran yang masih berpusat pada guru, minimnya keterlibatan aktif peserta didik, serta kurangnya penggunaan model pembelajaran yang kontekstual dan menantang daya berpikir kritis. Penelitian ini bertujuan untuk meningkatkan hasil belajar dan kualitas proses pembelajaran Pendidikan Agama Islam melalui penerapan model Problem Based Learning (PBL). Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, dengan setiap siklus meliputi tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah peserta didik kelas X SMA Negeri 1 Pulau Banyak. Teknik pengumpulan data dilakukan melalui tes hasil belajar, observasi aktivitas peserta didik, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan model Problem Based Learning mampu meningkatkan hasil belajar peserta didik secara signifikan, ditandai dengan peningkatan ketuntasan belajar dari 40% pada pra siklus menjadi 60% pada siklus I, dan meningkat kembali menjadi 87% pada siklus II. Selain itu, pembelajaran berbasis masalah terbukti meningkatkan keaktifan, partisipasi, serta kemampuan peserta didik dalam memahami materi PAI secara lebih mendalam dan kontekstual. Novelty penelitian ini terletak pada integrasi model Problem Based Learning dalam pembelajaran Pendidikan Agama Islam di tingkat Sekolah Menengah Atas yang tidak hanya berorientasi pada peningkatan hasil belajar, tetapi juga pada penguatan kemampuan berpikir kritis dan pemecahan masalah keagamaan yang relevan dengan kehidupan sehari-hari. Penelitian ini merekomendasikan penerapan model PBL secara berkelanjutan sebagai alternatif pembelajaran inovatif dalam mata pelajaran Pendidikan Agama Islam.]